Clinical characteristics and survival of systemic sclerosis patients with pulmonary hypertension and elevated wedge pressure: Observations from the PHAROS cohort. Issue 7 (12th May 2017) - Lammi, Matthew R.; Saketkoo, Lesley A.; Gordon, Jessica K.; Lauto, Paula; Fagan, Karen; Steen, Virginia D.; ,
ABSTRACT: Background and objective: Systemic sclerosis (SSc) is a complex autoimmune disease commonly associated with pulmonary hypertension (PH). When associated with elevated pulmonary artery wedge pressure (PAWP), pulmonary artery pressure (PAP) is either in‐proportion (post‐capillary PH) or higher than expected (combined PH) relative to the increased PAWP. Methods: Patients from the PHAROS registry (a prospective observational cohort of SSc‐PH patients) who had mean PAP ≥ 25 and PAWP > 15 on right heart catheterization were stratified based on diastolic pressure gradient (DPG). Kaplan–Meier analysis was performed to compare survival and PH‐related hospitalization. Baseline factors were compared between patients dying and those who survived using Cox regression analysis. Results: A total of 59 patients were included, of whom 21 (36%) patients were classified as combined PH and 38 (64%) had post‐capillary PH. No baseline characteristics were significantly different between the two groups. There were no differences in survival or PH‐related hospitalization between the groups. The only baseline factor independently associated with death was lower 6‐min walk distance (6MWD) (hazard ratio (HR): 1.33 per 25 m decrease, 95% CI: 1.11–1.59, P  = 0.002). PH‐specific medications were started during follow‐up in significantly more patients in the combined PH group compared with the post‐capillary group (86% vs 50%, P  = 0.01). Conclusion: Outcomes were similar between SSc patients with post‐capillary PH and combined pre‐ and post‐capillary PH. 6MWD at baseline can predict risk for death in SSc patients with PH and an elevated PAWP. More patients with combined PH were started on PH‐specific medications, and the clinical benefit of treating this subgroup specifically in SSc patients needs further exploration. Abstract : We analysed data for 59 patients with systemic sclerosis‐pulmonary hypertension (PH) and an elevated wedge pressure and found that there was no difference in clinical outcomes between those with post‐capillary PH and combined pre‐ and post‐capillary PH. The 6‐min walk distance was a predictor of death in this group.